1981
DOI: 10.1176/ajp.138.6.790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cost benefits of liaison psychiatry

Abstract: A liaison psychiatrist participated in the postoperative care of a group of elderly patients who underwent surgery for fractured femurs. Clinical outcomes for this group were compared with a control group of patients who were not treated by a liaison psychiatrist. Length of stay for the treatment group was 12 days shorter than for the control group, and twice as many patients in the treatment group returned home rather than being discharged to a nursing home or other health-related institution; therefore, a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…11 Depression can also interfere with a patient's participation in rehabilitative and other measures, resulting in prolonged stay. 12,13 In our study, CD patients had a 2-day longer inpatient stay than UC patients, which may be due to an increased number of admissions for CD and an increased number of surgeries. 14 UC and CD were associated with an increased risk of depression in our analysis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…11 Depression can also interfere with a patient's participation in rehabilitative and other measures, resulting in prolonged stay. 12,13 In our study, CD patients had a 2-day longer inpatient stay than UC patients, which may be due to an increased number of admissions for CD and an increased number of surgeries. 14 UC and CD were associated with an increased risk of depression in our analysis.…”
Section: Discussionmentioning
confidence: 62%
“…Conversely, patients without depression would not have as many confounding symptoms, resulting in a more accurate description of symptoms. 12 Subanalysis in the depressed cohort revealed that patients with CD had increased hospital charges of $17,974 compared to UC patients. Patients with CD had a higher medical cost, especially for the initial diagnosis, than patients with UC.…”
Section: Discussionmentioning
confidence: 99%
“…Psychotherapeutic models should comprehensively include collaboration between mental health specialists (psychologists, psychiatrists, social workers and neurologists). The task of future studies should be to carry out prospective, randomized and controlled psychosocial intervention studies investigating the efficacy of psychosomatic and psychosocial care in dermatology and, in particular, with certain skin disorders, as has already been done for other clinical specialties [30, 31, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, elderly patients with a fractured femur, with liaison psychiatrist input, were twice as likely to be discharged home and had a shorter length of stay, compared to patients with no psychiatric involvement [20]. Desan and his colleagues found that psychiatric consultation reduces length of stay for medical inpatients [21].…”
Section: Introductionmentioning
confidence: 99%